Finland's balance of payments, 1890-1913 - Ragni Bärlund (Bank of Finland, 1992)
Ragni Bärlund worked in the Bank of Finland Institute for Economic Research (tilI 1944 The Statistical Department) from 1938 to. 1963. During those years one of her main interests was to colIect Finland's balance of payments. Ragni Bärlund's calculations for the interwar. period 'were published in the Bank of Finland Monthly Bulletin and in the Yearbook of the League of Nations. After she had retired in 1963, RagIii Bärlund" continued collecting balance of payments data conceming the years 1890-1913. Because of some uncertainty and missing data, Bärlund hesitated to publish her manuscript after finishing the study in the mid-1960s. Now, after twentyfive years there are still no better calculations of the balance of payments statistics for the end of the autonomous time. In addition, recent studies seem to prove that Bärlund's figures are reliable both from a historical and a macroeconomic point of view. Of course, there are always some parts of the balance of payments that cannot be calculated exactly. The worst problems are in regard to trade of services. Anyhow, Bärlund's figures do not contradict other historians' more descriptive calculations. The footnotes in the following article are mostly Bärlund's own comments considering sources and calculating methods. The editor's footnotes include mostly comparisons to other studies published after the 1960s. Besides, all figures are in current prices and in millions of "old marks" (100 mark 1962 = 1 mark of 1963).
URN:NBN:fi:bof-201808021872
Keywords: 330